Unicentric Castleman's Disease of Paraspinal Origin Requiring Differentiation From Schwannoma: Case Report - Hazuki Fujimoto; Kayoko Okamura; Shunsuke Tauchi; Rei Tsukamoto; Nanami Kida; Miho Ikeda; Yukihisa Hatakeyama; Hisashi Ohnishi (Respirology Case Reports)
ABSTRACT Unicentric Castleman's disease (UCD) typically presents as an asymptomatic tumour in the anterior or middle mediastinum. Occurrence in the paravertebral region is comparatively rare and it requires differentiation from neurogenic tumours by imaging. In our patient, preoperative imaging findings were atypical of schwannoma. Contrast‐enhanced MRI of the thoracic region showed a muscle‐like mass in contact with the pleura on T1‐weighted images. T2‐weighted images showed high signal, especially at the margins. Diffusion‐weighted images showed diffusion restriction around the limbus, and contrast‐enhanced T1‐weighted images displayed strong enhancement of the mass. Diagnosis could not be made preoperatively, although UCD was suspected. Thoracoscopic tumour resection was performed for definitive diagnosis and treatment and postoperative diagnosis was hyaline‐vascular‐type UCD. Diagnosis of neurogenic tumours can be difficult by imaging alone. When imaging findings are atypical, a definitive diagnosis is required, with consideration of the possibility of UCD.